An evaluation of interdependent and independent group contingencies during the good behavior game. Issue 3 (13th May 2017) - Groves, Emily A.; Austin, Jennifer L.
Abstract : The Good Behavior Game (GBG) uses an interdependent group contingency to improve classroom behavior. Despite the wealth of research on the effectiveness of the GBG, some teachers may have concerns about their students' abilities to work in teams, particularly if they have a history of poor social skills. We used an alternating treatments design to compare the relative effectiveness of the GBG with interdependent and independent group contingencies in a classroom for children with emotional and behavioral disorders. Our results showed that both versions of the GBG reduced verbal disruptions, inappropriate sitting, and off‐task behaviors for all children. However, the majority of children preferred the interdependent arrangement. We discuss how these results may promote more widespread use of the GBG with children with substantial behavioral challenges.